MODERASI BERAGAMA PERSPEKTIF AGAMA-AGAMA DI INDONESIA - Amri, Khairul (Living Islam: Journal of Islamic Discourses, 2021)
AbstractReligious moderation is a religious perspective, attitude and behavior that always takes in a middle position, acts fairly, and is not a religious extreme. In this case, The government, namely the Ministry of Religious Affairs, considers to strengthens religious moderation as a strategic effort in building the integrity of the nation. As a pluralistic country, religious moderation is very needed as an effort to build national harmony and sustainability. The term of religious moderation is often identified with wasathiyah in Islam, but in fact the principles of religious moderation are stated in every religious teaching of all religions. They all require peace, justice, and maintain human values. This is the important of understanding that the very basic religious teachings are in line with the religious moderation.Key words: religious moderation, pluralistic society, Indonesia. AbstrakModerasi Beragama adalah sebuah cara pandang, sikap dan perilaku beragama yang selalu mengambil posisi di tengah-tengah, selalu bertindak adil, dan tidak ekstrem dalam beragama. Pemerintah dalam hal ini Kementerian Agama menganggap penguatan moderasi beragama sebagai upaya strategis dalam menjaga keutuhan bangsa. Sebagai negara yang majemuk, cara pandang moderasi beragama sangat dibuthkan sebagai usaha untuk menjaga kerukunan dan kelestarian bangsa. Terminologi moderasi beragama sering diidentikkan dengan wasathiyah dalam Islam, namun seseungguhnya prinsip-prinsip moderasi beragama terdapat dalam setiap ajaran agama-agama, sebab sejatinya ajaran agama selalu menghendaki perdamain, keadilan, dan menjaga nilai-nilai kemanusiaan. Hal ini penting untuk dipahami sebagai pengetahuan bahwa esensi setiap ajaran agama sejalan dengan prinsip-prinsip moderasi beragama.